The South African Nursing Association - Quo Vadis - M.C. van Huyssteen (AOSIS, 1984)
The S.A. Nursing Association, as defined in Section 38 of the Nursing Act 1978 (No.50 of 1978), as amended, represents the profession of nursing and midwifery in the Republic of South Africa. It is therefore a statutary body and has been one since 1944 when the first Nursing Act was promulgated.